If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4b+6=-b-4
We move all terms to the left:
4b+6-(-b-4)=0
We add all the numbers together, and all the variables
4b-(-1b-4)+6=0
We get rid of parentheses
4b+1b+4+6=0
We add all the numbers together, and all the variables
5b+10=0
We move all terms containing b to the left, all other terms to the right
5b=-10
b=-10/5
b=-2
| 6x-10x=64 | | y+4.7=7.45 | | 17n=306 | | -8+h4=13 | | -11/t=11 | | x*2/5=1 | | -96=-4(4+4n) | | (n-5)/(10)=-5 | | 5(3n-8)=-1+2n | | -3(3x-2)=4x-8+3x | | 5/6h-9=4 | | 5x-25=18+5x | | 1/3x-4=1/4x+3 | | 15-10x-15=80.5 | | 2n+4=n/3 | | -0.62x+0.32x=6.6 | | -2x+3/4=-4-x | | 1-5m=-19 | | 7x+8=x-46 | | 0=-2+v/6 | | 4(12x-12)=240 | | -8(8+3v)=-8v | | 5x+4-7=0 | | 4x-6+2=16 | | 2x-14=34 | | 3.5=2r/7 | | 51=(x-1)+(x-1)+(x-3) | | 4(0.5f-0.25f)=6+f | | -(-3x+5)=-14 | | -20r^2+41r-20=0 | | 11x+9=135 | | 20b+13=13 |